Prinsepiae Nux Extract Activates NRF2 Activity and Protects UVB-Induced Damage in Keratinocyte - Shih-Han Wang; Yi-Siao Chen; Kuei-Hung Lai; Chung-Kuang Lu; Hsun-Shuo Chang; Ho-Cheng Wu; Feng-Lin Yen; Lo-Yun Chen; Jin-Ching Lee; Chia-Hung Yen (MDPI AG, 2022)
Ultraviolet B (UVB) is one of the most important environmental factors that cause extrinsic aging through increasing intracellular reactive oxygen species (ROS) production in the skin. Due to its protective roles against oxidative stress, nuclear factor erythroid-2-related factor (NRF2) has been traditionally considered as a target for skin aging prevention. Here, we identified the extract of Prinsepiae Nux, a top-grade drug listed in Shen Nong Ben Cao Jing, as a potent NRF2 activator by high-throughput screening. A bioassay-guided fractionation experiment revealed that NRF2-activating components were concentrated in the 90% methanol (MP) fraction. MP fraction significantly increased the expression of NRF2 and HO-1 protein and upregulated HO-1 and NQO1 mRNA expression in HaCaT cells. Moreover, MP fraction pre-treatment dramatically reversed UVB-induced depletion of NRF2 and HO-1, accumulation of intracellular ROS, NF-κB activation, and the upregulation of pro-inflammatory genes. Finally, the qualitative analysis using UPLC-tandem mass spectroscopy revealed the most abundant ion peak in MP fraction was identified as α-linolenic acid, which was further proved to activate NRF2 signaling. Altogether, the molecular evidence suggested that MP fraction has the potential to be an excellent source for the discovery of natural medicine to treat/prevent UVB-induced skin damage.